The Bee Symbolism in Sylvia Plath’s Poetics – Between Rational and Inspiration - Mušović, Azra (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Contemporary American poetess of confessional orientation, Sylvia Plath, was often in her career torn between the rational role-models and creative inspiration. This tension is most evident in Plath’s metaphors, in which her desire for control and understanding is confronted to the limitations of language to signify the unspoken. The paper aims at presenting symbolic (psychological, religious) semantics of bees in the author’s literary oeuvre. The bees are an appropriate, uncrystallized medium; like language, they resist comparison through their transformative power. The bee becomes a personal emblem of the poetess; it represents the culmination and reconciliation of the classical and rational influences in her poetics. The cyclical nature of the bee poems follows the pattern of symbolic death and rebirth—signifying a regeneration—the spring of a new life. Although the spring will inevitably lead one more time to winter and death, the bee as a medium has a liberating quality for the poetess, signifying vitality and authenticity that remain the ultimate values of her art.